Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Sosiologi di SMA Negeri 7 Kota Serang - Naim, Mochammad; Fauzi, Agung; Pratama, Ahmad; Fitriani, Annisa; Balqis, Azmelia Putri; Raisya, Hanna; Zahra, Marisatu; Sari, Nawang; Brilyando, Rama Shaquilla; Indriyani, Rahma Agung Dira; Amanda, Rahma; Yulianti, Yulianti (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
This research was motivated by the use of conventional learning models at SMAN 7 Serang City which had an influence on student learning outcomes that were less than optimal. The aim of this research is to determine whether the project based learning model can improve student learning outcomes in sociology subjects at SMAN 7 Serang City. In this research, researchers used a qualitative approach and used descriptive research methods. The results of the research are that the application of the project based learning model in class XII IPS can improve student learning achievement. This is reflected in the students' pre-test results by giving several questions in a quiz and they can explain the results of their work in front of the class.